A Diol-Based-Matrix Solid-Phase Dispersion Method for the Simultaneous Extraction and Determination of 13 Compounds From Angelicae Pubescentis Radix by Ultra High-Performance Liquid Chromatography - Ding, Mingya; Bai, Yun; Li, Jin; Yang, Xuejing; Wang, Hui; Gao, Xiumei; Chang, Yan-xu (Frontiers in Pharmacology, 2019)
A simple and eco-friendly Diol-based-matrix solid-phase dispersion method (MSPD) was optimized and established to simultaneously extract 13 bioactive compounds (7 coumarins and 6 phenolic acids) in Angelicae Pubescentis Radix (APR) by ultrahigh performance liquid chromatography coupled with photodiode array detector (UHPLC-PDA). Diol was chosen as the dispersing sorbent and methanol solution was used as the elution solvent. The preparation procedures for the MSPD including the types of sorbents, mass ratio of matrix to sorbent, grinding time, type, concentration and volume of elution solvent were investigated. Under the optimal conditions, good recoveries of the 13 target compounds were obtained in the range of 94.8-107% (RSD < 3.22%). The limits of detection (LODs) and limits of quantitation (LOQs) were in the ranges of 0.08-0.12 g mL-1 and 0.16-0.24 g mL-1, respectively. Compared with the traditional method, it was a green and environmentally friendly technique. The results proved that the established method was successfully applied to the extraction and determination of 13 target bioactive compounds for quality control in APR.